Leishmania mexicana: Novel Insights of Immune Modulation through Amastigote Exosomes - Laura Enedina Soto-Serna; Mariana Diupotex; Jaime Zamora-Chimal; Adriana Ruiz-Remigio; José Delgado-Domínguez; Rocely Buenaventura Cervantes-Sarabia; Adriana Méndez-Bernal; Alma Reyna Escalona-Montaño; María Magdalena Aguirre-García; Ingeborg Becker (Journal of Immunology Research)
Exosomes are extracellular microvesicles of endosomal origin (multivesicular bodies, MVBs) constitutively released by eukaryotic cells by fusion of MVBs to the plasma membrane. The exosomes from Leishmania parasites contain an array of parasite molecules such as virulence factors and survival messengers, capable of modulating the host immune response and thereby favoring the infection of the host. We here show that exosomes of L. mexicana amastigotes (aExo) contain the virulence proteins gp63 and PP2C. The incubation of aExo with bone marrow-derived macrophages (BMMs) infected with L. mexicana led to their internalization and were found to colocalize with the cellular tetraspanin CD63. Furthermore, aExo inhibited nitric oxide production of infected BMMs, permitting enhanced intracellular parasite survival. Expressions of antigen-presenting (major histocompatibility complex class I, MHC-I, and CD1d) and costimulatory (CD86 and PD-L1) molecules were modulated in a dose-dependent fashion. Whereas MHC-I, CD86 and PD-L1 expressions were diminished by exosomes, CD1d was enhanced. We conclude that aExo of L. mexicana are capable of decreasing microbicidal mechanisms of infected macrophages by inhibiting nitric oxide production, thereby enabling parasite survival. They also hamper the cellular immune response by diminishing MHC-I and CD86 on an important antigen-presenting cell, which potentially interferes with CD8 T cell activation. The enhanced CD1d expression in combination with reduction of PD-L1 on BMMs point to a potential shift of the activation route towards lipid presentations, yet the effectivity of this immune activation is not evident, since in the absence of costimulatory molecules, cellular anergy and tolerance would be expected.